Does exposure to cigarette brands increase the likelihood of adolescent e-cigarette use? A cross-sectional study. Issue 2 (23rd February 2016) - Best, C; van der Sluijs, W; Haseen, F; Eadie, D; Stead, M; MacKintosh, AM; Pearce, J; Tisch, C; MacGregor, A; Amos, A; Miller, M; Frank, J; et al.
Abstract : Objective: To examine the relationship between tobacco cigarette brand recognition, and e-cigarette use in adolescents. Design: Cross-sectional observational study. Setting: High schools in Scotland. Participants: Questionnaires were administered to pupils in Secondary 2 (S2 mean age: 14.0 years) and Secondary 4 (S4 mean age: 15.9 years) across 4 communities in Scotland. An 86% response rate with a total sample of 1404 pupils was achieved. Main outcome measures: Self-reported previous use of e-cigarettes and self-reported intention to try e-cigarettes in the next 6 months. Results: 75% (1029/1377) of respondents had heard of e-cigarettes (69.5% S2, 81.1% S4), and of these, 17.3% (10.6% S2, 24.3% S4 n=1020) had ever tried an e-cigarette. 6.8% (3.7% S2, 10.0% S4 n=1019) reported that they intended to try an e-cigarette in the next 6 months. Recognition of more cigarette brands was associated with greater probability of previous e-cigarette use (OR 1.20, 99% CI 1.05 to 1.38) as was having a best friend who smoked (OR 3.17, 99% CI 1.42 to 7.09). Intention to try e-cigarettes was related to higher cigarette brand recognition (OR 1.41, 99% CI 1.07 to 1.87), hanging around in the street or park more than once a week (OR 3.78, 99% CI 1.93 to 7.39) and living in areas of high tobacco retail density (OR 1.20, 99% CI 1.08 to 1.34). Never having smoked was a protective factor for both future intention to try, and past e-cigarette use (OR 0.07, 99% CI 0.02 to 0.25; and OR 0.10, 99% CI 0.07 to 0.16, respectively). Conclusions: Higher cigarette brand recognition was associated with increased probability of previous use and of intention to use e-cigarettes. The impact of tobacco control measures such as restricting point-of-sale displays on the uptake of e-cigarettes in young people should be evaluated.